Association of mitochondrial genomic background with risk of Multiple System Atrophy. (December 2020) - Valentino, Rebecca R.; Heckman, Michael G.; Johnson, Patrick W.; Soto-Beasley, Alexandra I.; Walton, Ronald L.; Koga, Shunsuke; Uitti, Ryan J.; Wszolek, Zbigniew K.; Dickson, Dennis W.; Ross, Owen A.
Abstract: Introduction: Multiple system atrophy (MSA) is a rare, sporadic, and progressive neurodegenerative disease which is characterized neuropathologically by alpha-synuclein aggregates in oligodendroglia, and clinically by parkinsonism, ataxia, and autonomic dysfunction. Mitochondrial health influences neurodegeneration and defects in mitochondria, particularly in oxidative phosphorylation, are reported in MSA. Mitochondrial DNA (mtDNA) codes for 13 critical OXPHOS proteins, however no study has investigated if mtDNA variation, in the form of mitochondrial haplogroups, influences MSA risk. Therefore, in this study we investigated the association of mtDNA haplogroups with MSA risk in a case-control manner. Methods: 176 pathologically confirmed MSA cases and 910 neurologically healthy controls from Mayo Clinic Jacksonville were genotyped for 39 unique mtDNA variants using Agena Biosciences MassARRAY iPlex technology. Mitochondrial haplogroups were assigned to mitochondrial phylogeny, and logistic regression models that were adjusted for age and sex were used to assess associations between mitochondrial haplogroups and risk of MSA. Results: After adjusting for multiple testing (P<0.0019 considered significant), no mitochondrial haplogroups were significantly associated with MSA risk. However, several nominally significant (P<0.05) associations were observed; haplogroup I was associated with a decreased risk of MSA (OR=0.09, P=0.021), while an increased risk of MSA was observed for haplogroups H3 (OR=2.43, P=0.017) and T1 and T2 (OR=2.04, P=0.007). Conclusion: This study investigated whether population-specific mtDNA variation is associated with risk of MSA, and our nominally significant findings suggest mitochondrial haplogroup background may influence MSA risk. Validation of these findings and additional meta-analytic studies will be important. Highlights: Stable variations in mitochondrial DNA change oxidative phosphorylation efficiency. Custom-designed genetic arrays defined specific mitochondrial DNA haplogroups. Mitochondrial haplogroups H3 and T suggest increased risk of Multiple system atrophy. Mitochondrial haplogroup background may influence Multiple system atrophy subtypes. Stable mitochondrial variations may influence α-synuclein aggregation patterns.